Frequency and Morbidity Associated With Flat Foot Anomaly Among School Going Children - Gohar, Awais; Shah, Farhan; Hassan, Syed Bilal; Khan, Iqra Hamid (Biological and Clinical Sciences Research Journal, 2025)
Flat foot anomaly, commonly seen in children, occurs when the foot’s arch is flattened, leading to potential orthopedic complications that can affect mobility and physical activity. Objective: To explore the prevalence and impact of flat feet on foot health, daily functioning, and long-term well-being. Methodology: This cross-sectional study assessed the prevalence and morbidity of flat foot anomaly in school children aged 7 to 14 years in Lahore, using the Plantar Arch Index (SPI) and Foot Health Status Questionnaire (FHSQ). Data analysis was performed using SPSS, with descriptive statistics and Pearson’s Chi-square test, considering a p-value of ≤ 0.05 as significant. Results: The study included 223 male participants with a mean age of 10.14 ± 2.45 years, where 62.3% (139 participants) were normal weight, and 19.7% (44 participants) had flat feet. A significant association was found between BMI and foot status (p = 0.000*), with underweight children having more flat feet. Pain location (p = 0.005*) and pain level (p = 0.041*) were also significantly associated with flat foot prevalence, along with differences in pain (p = 0.050*) and foot health status (p < 0.001*). Conclusion: This study highlights the significant impact of flat foot anomalies on pain tolerance and foot health, emphasizing the importance of early identification and intervention to prevent complications in school-aged children.